Harga Diri dan Kematangan Karir Pada Siswa Sekolah Menengah Kejuruan - Marita, Rizka Hasna; Izzati, Umi Anugerah (Universitas Negeri Surabaya, 2017)
The purpose of this study was to determine the relationship between self-esteem and career maturity among students of Ketintang Vocational High School Surabaya (Sekolah Menengah Kejuruan/SMK Ketintang Surabaya) majoring in accounting. This study used a quantitative approach with correlation design. The total of 105 students were involved as the sample. Instruments used to collect data were the scales of self-esteem, and career maturity. Data were analyzed using product moment correlation technique to find the relationship between the two variables. The result shows the correlation coefficient between self-esteem and career maturity is 0.518 (r = 0.518) with a significant value of 0.000 (p = 0.000). It can be concluded from the result that there is a relationship between self-esteem and career maturity. It indicates that the higher self-esteem the students have will result in the higher level of their career maturity. Abstrak: Tujuan penelitian ini adalah untuk menguji hubungan antara harga diri dengan kematangan karir pada siswa jurusan akuntansi di SMK Ketintang Surabaya. Metode penelitian kuantitatif digunakan dengan subjek berjumlah 105 siswa sebagai sampel. Instrumen yang digunakan adalah skala harga diri dan skala kematangan karir. Teknik analisa data yang digunakan adalah teknik korelasi Product Moment untuk mencari hubungan antara dua variabel. Hasil analisis antara harga diri dengan kematangan karir menunjukkan koefisien korelasi sebesar 0,518 (r = 0,518) dengan nilai signifikan sebesar 0,000 (p = 0,000) artinya ada hubungan antara harga diri dengan kematangan karir. Semakin tinggi nilai harga diri siswa maka semakin meningkat pula tingkat kematangan karirnya.